Violence against the elderly - analysis of further research needs based on a systematic review of research - Primc, Teja (Varstvoslovje, 2021)
Purpose of the Paper: The purpose of this paper is to investigate the current state of research on the topic of elder abuse both in the institutional and domestic environment and to present the key findings of existing studies. The paper also aims to shed light on areas requiring additional research and present the directions for further research. Methods: A systematic literature review was conducted using the PRISMA method in the Web of Science and Scopus databases. The review included 29 papers published between 2010 and 2021. Findings: Elder abuse is an under-researched topic. The lack of research is particularly apparent in the incidence and nature of the problem in the home environment. Previous studies focus on the various forms of abuse, its perpetrators and risk factors. Rates of psychological abuse, neglect and physical abuse are high in nursing homes and among older visitors to ambulatory care facilities and emergency departments, while self-neglect, neglect and psychological abuse are prevalent in the home environment. Women between the ages of 70 and 75, who are socially isolated and require daily care, are more exposed to abuse. The perpetrators of the abuse are most often family members. Limitations/Applicability of the Research: The ‘paper’s findings provide insight into research on elder abuse and can serve as a basis for planning research into this phenomenon. The paper highlights research gaps and introduces opportunities for improvements in the systemic approaches when addressing the issue. Originality/Relevance of the Paper: The paper presents the systematic and up to date analysis of past studies on elder abuse. The results are intended for professionals and researchers working in the field.
Keywords: abuse; elderly; nasilje; neglect; sistematični pregled literature; starostniki; systematic literature review; violence; zanemarjanje; zloraba